2011
DOI: 10.1103/physrevc.83.055202
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of the resonantΛ(1405) state in chiral dynamics

Abstract: The internal structure of the resonant (1405) state is investigated based on meson-baryon coupled-channels chiral dynamics by evaluating density distributions obtained from the form factors of the (1405) state. The form factors are defined as an extension of the ordinary stable particles and are directly evaluated from the currentcoupled meson-baryon scattering amplitude, paying attention to the charge conservation of the probe interactions. For the resonant (1405) state we calculate the density distributions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 69 publications
3
78
0
Order By: Relevance
“…The compositeness condition was extended leading to a new sum rule in an arbitrary number of coupled channels [13], which is reformulated in [14][15][16][17][18] for the case of energy dependent potentials. The sum rule contains two terms (see eq.…”
Section: Jhep05(2015)153mentioning
confidence: 99%
“…The compositeness condition was extended leading to a new sum rule in an arbitrary number of coupled channels [13], which is reformulated in [14][15][16][17][18] for the case of energy dependent potentials. The sum rule contains two terms (see eq.…”
Section: Jhep05(2015)153mentioning
confidence: 99%
“…[65]. Based on this normalization, we propose to interpret the compositeness X i and elementariness Z for a certain class of resonances on the basis of the similarity to the bound state case.…”
Section: A Chiral Unitary Approach and Compositenessmentioning
confidence: 99%
“…In fact, the spatial size of exotic hadron candidates was theoretically measured in a meson-meson and meson-baryon scatterings in, e.g., Refs. [65][66][67][68], and it was found that f 0 (980) and Λ(1405), whose KK andKN compositeness are close to unity, respectively, has spatial size exceeding largely the typical hadronic scale 0.8 fm.…”
mentioning
confidence: 99%
“…For the confirmation of the dominance of such aKN molecular component in the Λ(1405), the concept of the compositeness has been used in recent works [9,10]. The spatial structure of the Λ(1405) has been discussed with the form factors and finite volume effect [11][12][13]. As an alternative way for the confirmation, in this work, we study the spatial extent of the Λ(1405) from theKN wave function, considering that the hadronic molecular states would have the relatively larger size than usual hadrons [14].…”
Section: Introductionmentioning
confidence: 99%